Control of Iron Disilicide Crystal Structure by Using Liquid Phase Obtained by Au-Si Eutectic Reaction. Issue 1760 (4th February 2015) - Baker, I.; Heilmaier, M.; Kishida, K.; Mills, M.; Miura, S.; Akiyama, Kensuke; Motoizumi, Yuu; Funakubo, Hiroshi
ABSTRACT The Au-Si liquid phase was obtained by melting the Si surface via Au-Si eutectic reaction, which contributed to the formation of semiconducting iron disilicide (Î²-FeSi2), on Au-coated Si(100) substrates. By coating a substrate with an Au layer of 60 nm or more, the Au-Si liquid phase covered the entire Si substrate surface, and single-phase Î²-FeSi2 was grown on Si(100) substrates. A clear photoluminescence spectrum of Î²-FeSi2 indicated the formation of high-quality crystals with a low density of the non-radiative recombination center in the grains.